Smart Campus Governance Design for XYZ Polytechnic Based on COBIT 2019 - Ryan Adhitya Nugraha; Ratih Syaidah (Society of Visual Informatics, 2022)
Technological developments drive growth in the industrial revolution and digital transformation era. Technological developments during the industrial revolution 4.0 affect characteristics, especially in work. In responding to the change in technological developments in employment, the Ministry of Public Works has the task of conducting public works affairs in the government environment in an orderly manner to support the president in administering state government. XYZ Polytechnic is a state university as a new pilot under the Ministry of Public Works, Republic of Indonesia. As a basis for future development as well as towards a smart campus and then getting policy directions for the development of smart campus governance at the XYZ Polytechnic, it is necessary to design IT governance, especially in the reconstruction of adaptive and responsive policies and the development of structured governance with structured information systems. This study uses COBIT 2019 as the framework for governance design. With the method from the field preparation stage, interviews then assessed and evaluated existing policies and conditions of field activities to create governance designs according to COBIT 2019. The research results contained a technology governance management design with 17 processes. Based on the capability assessment and gap analysis results, recommendations were made for XYZ Polytechnic, as discussed in the results section. The suggestions are in the form of recommendations related to people, processes, and the use of technology. The recommendations act as evaluation material to improve organizational performance by providing good smart campus governance to students and internal members of XYZ Polytechnic.